2021
DOI: 10.1007/s00521-020-05641-9
|View full text |Cite
|
Sign up to set email alerts
|

Triage of potential COVID-19 patients from chest X-ray images using hierarchical convolutional networks

Abstract: The current COVID-19 pandemic has motivated the researchers to use artificial intelligence techniques for a potential alternative to reverse transcription-polymerase chain reaction due to the limited scale of testing. The chest X-ray (CXR) is one of the alternatives to achieve fast diagnosis, but the unavailability of large-scale annotated data makes the clinical implementation of machine learning-based COVID detection difficult. Another issue is the usage of ImageNet pre-trained networks which does not extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Compared with the CNN-LSTM and CNN-GRU models, the proposed model generated the best results [ 116 ]. Dev et al suggested a hierarchical convolutional network and produced better results than prior studies [ 117 ].…”
Section: Automated Computational Methods For Diagnosis Of Malariamentioning
confidence: 99%
“…Compared with the CNN-LSTM and CNN-GRU models, the proposed model generated the best results [ 116 ]. Dev et al suggested a hierarchical convolutional network and produced better results than prior studies [ 117 ].…”
Section: Automated Computational Methods For Diagnosis Of Malariamentioning
confidence: 99%
“…Higher values of metrics indicate the best quality of fused images. Its value ranges in the interval of 0 to 1 where 1 or more than 1 indicates the enhanced quality image [43][44][45]. Tab.…”
Section: Objective Visibilitymentioning
confidence: 99%
“…Google's speech recognition and search packages in python help in performing such tasks. 2 As mentioned Fig. 1 The physical healthcare monitoring module for patient monitoring during the isolation phase.…”
Section: Neural Computing and Applicationsmentioning
confidence: 99%
“…The contraction of COVID-19 causes loss of smell and taste, breathing problems, cough, and fever, respectively. The extended length of the aforementioned symptoms in vulnerable patients might result in heart issues, respiratory problems, hypertension, organ failure, and in the worst case death [2]. In the beginning, older populations were considered to be at risk, but as per WHO guidelines ''the children and young people are not invulnerable to this virus'' [3].…”
Section: Introductionmentioning
confidence: 99%